Anatomy of the Cystic Duct – Factors Affecting the Stasis of Bile and Formation of Gall Stones (Bangladesh Journal of Anatomy, 2015)
Background: An increasing incidence of liver and gall bladder diseases bring about an increasing necessity of their precise diagnosis. Unrecognized anatomic variants of the extrahepatic billiary apparatus may cause confusion on imaging studies and complicate subsequent surgical, endoscopic, and percutaneous procedures. Although much have been written about the normal anatomy and related diseases of the gallbladder and biliary tract but no available data have been found about the variations of the cystic duct in Bangladeshi people. This study was aimed at determining the anatomical variations of gross morphological features of cystic duct in relation to age and sex in Bangladeshi people as well as to find out any congenital anomalies of the extrahepatic biliary system.Materials and methods: A cross sectional descriptive type of study was carried out at the Department of Anatomy, Rangpur Medical College, Rangpur. The study was conducted on postmortem gallbladder with cystic duct from 60 unclaimed dead bodies of Bangladeshi people. Of which, 32 were male specimens and 28 were female specimens. The specimens were divided into two groups according to age, young age group A (20-40 years) and elderly age group B (41-65 years). The length and diameter of cystic duct was measured and number of valves in cystic duct was counted. Comparison was done between male and female of two age groups by Student’s unpaired‘t’ test.Results: The length of the cystic duct showed a significantly higher value in elderly male than younger male and corresponding f emale groups of similar age. The number of spiral valves showed similar values in both sexes.Conclusion: No relationship between cystic duct length, diameter and number of spiral valves with different sex and different age could be established in this study.Bangladesh Journal of Anatomy July 2015, Vol. 13, No. 2, pp. 32-36